2013
DOI: 10.1021/jf3043083
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment of the Exposure of Insecticide Operators to Fenvalerate during Treatment in Apple Orchards

Abstract: Dermal and inhalation exposure of the applicator to the insecticide fenavalerate in an apple orchard was measured for risk assessment during treatment. Emulsifiable concentrate (EC) and wettable powder (WP) formulations were sprayed using a speed sprayer (SS) or power sprayer (PS). Dermal patches, gloves, socks, and masks were used to monitor potential dermal exposure to fenavalerate, while personal air samplers with XAD-2 resins were used to monitor potential inhalation exposure. Validation of analytical meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
45
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 21 publications
(43 reference statements)
13
45
1
2
Order By: Relevance
“…These data were in accordance with previous values for methomyl (0.01-0.04%) and fenvalerate (0.008-0.054%) in apple orchard. (24,25) By contrast, a greater value (0.18-0.34%) was obtained for cypermethrin in a mandarin field. (11) The mean inhalation exposure of flonicamid was 0.7 µg (range: 0.031-1.7 µg) during application, corresponding to 1.4×10 −6% of the applied amount (Table 2), being smaller to a prior report 9.81×10 −6% for EC and 8.65×10 −6% for WP in an apple orchard with fenvalerate.…”
Section: Dermal and Inhalation Exposure During Sprayingmentioning
confidence: 74%
See 2 more Smart Citations
“…These data were in accordance with previous values for methomyl (0.01-0.04%) and fenvalerate (0.008-0.054%) in apple orchard. (24,25) By contrast, a greater value (0.18-0.34%) was obtained for cypermethrin in a mandarin field. (11) The mean inhalation exposure of flonicamid was 0.7 µg (range: 0.031-1.7 µg) during application, corresponding to 1.4×10 −6% of the applied amount (Table 2), being smaller to a prior report 9.81×10 −6% for EC and 8.65×10 −6% for WP in an apple orchard with fenvalerate.…”
Section: Dermal and Inhalation Exposure During Sprayingmentioning
confidence: 74%
“…Similar results were reported by Moon, who showed that the primary body parts were thigh and upper arm for speed sprayer when fenvalerate was applied in apple orchards. (24) The data suggest that the potential inhalation exposure was small compared with the potential dermal exposure, and suggesting that wearing a facemask can effectively reduce inhalation exposure of flonicamid.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…호흡노출은 피부노출에 비해 대개 0.0-9.1% 이하로 그 양 이 적지만 (Culver et al, 1956;Miller et al, 1980;WHO, 1982;Wojeck et al, 1983;USEPA, 1996;Capri et al, 1999;Oliveira and Machado-Neto, 2003;Choi et al, 2006;Kim et al, 2011 a,b ;Kim et al, 2012 a,b ; Choi and Moon, 2013;Moon et al, 2013;Kim et al, 2014), 노출량 100% 가 몸에 흡수되는 것으로 가정하기 때문에 (Fenske and Day JR, 2005;Worgan, 2005, Kim et al, 2011 a, Choi and Moon, 2013;Moon et al, 2013;Kim et al, 2014) 위해평가 과정에서 기여도가 높으며, 특히 시설 재배 와 실내와 같은 밀폐된 공간에서의 농약 살포 시 호흡노출 은 매우 중요하다 (Castro Cano et al, 2000;Machera et al, 2003;Byoun et al, 2005;Ramos et al, 2010;Choi and Moon, 2013;Kim et al, 2014;An et al, 2015).…”
Section: 서 론unclassified
“…농작업자의 호흡노출량 측정은 일반적으로 XAD-2 등의 고체흡착제를 개인용 공기펌프에 연결하거나 (Farewell et al, 1977;Johnson et al, 1977;Lewis and Jackson, 1982;Billing and Bidleman, 1983;Williams et al, 1986;Leidy and Wright, 1991;Wright et al, 1993;Lu and Fenske, 1998;Machera et al, 2003;Byoun et al, 2005;Choi et al, 2006;Farahat et al, 2010;Kim et al, a,b , 2012Dalvie et al, 2014;An et al, 2014;Cao et al, 2015), 고체 흡착제 앞에 유리섬유여과지를 연결하여 사용하였다 a,b , Kim et al, 2012Choi and Moon., 2013;Moon et al, 2013;Zhao et al, 2015 (Katinka et al, 2004;Grobkopf et al, 2013;Kim et al, 2014) (Fig. 1).…”
Section: 서 론unclassified